Variability in clinicians' prediction accuracy for outcomes of adult cochlear implant users. - Philpott, Nikki; Philips, Birgit; Donders, Rogier; Mylanus, Emmanuel; Huinck, Wendy (International Journal of Audiology, 2024)
The variability in outcomes among adult cochlear implant (CI) users poses challenges for clinicians in accurately predicting the benefits of the implant for individual candidates. This study aimed to investigate the accuracy and confidence of clinicians in predicting speech perception outcomes for adult CI users one-year post-implantation. Participants were presented with comprehensive information on pre-implantation, one-month post-implantation, and six-month post-implantation data for 10 case studies. The cases encompassed a range of one-year post-implantation phoneme scores, from low performers (27%) to high performers (92%). Participants were tasked with predicting the speech perception outcomes for these cases one year after implantation. Forty-one clinicians completed the full outcome prediction survey. Our findings revealed a significant over-prediction of low performance by clinicians. Interestingly, clinicians tended to predict average performance (73–76% phoneme score) even when provided with information suggesting lower-than-average performance. Most clinicians expressed confidence in their predictions, irrespective of their accuracy. Identifying signs of low performance, particularly in the early post-implantation period, can enable clinicians to implement early interventions. Further research into accurate outcome prediction is essential for managing expectations, providing counselling, increasing CI adoption, and optimising clinical care for both high and low performers.